2017
DOI: 10.1063/1.4993118
|View full text |Cite
|
Sign up to set email alerts
|

High resolution structural characterisation of laser-induced defect clusters inside diamond

Abstract: Laser writing with ultrashort pulses provides a potential route for the manufacture of three-dimensional wires, waveguides, and defects within diamond. We present a transmission electron microscopy study of the intrinsic structure of the laser modifications and reveal a complex distribution of defects. Electron energy loss spectroscopy indicates that the majority of the irradiated region remains as sp3 bonded diamond. Electrically conductive paths are attributed to the formation of multiple nano-scale, sp2-bon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…High resolution transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) performed by the Salter group on femtosecond laser written tracks showed a non‐uniform structural modification consisting of 4% of sp 2 bonded carbon . The tracks were written using a femtosecond Ti:Sapphire laser at 1 kHz repetition rate.…”
Section: Photonic Components In Diamondmentioning
confidence: 99%
“…High resolution transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) performed by the Salter group on femtosecond laser written tracks showed a non‐uniform structural modification consisting of 4% of sp 2 bonded carbon . The tracks were written using a femtosecond Ti:Sapphire laser at 1 kHz repetition rate.…”
Section: Photonic Components In Diamondmentioning
confidence: 99%
“…One possible explanation is that microscopic gaps exist within the graphitic network of the wire, and that charge transport can only be achieved by surpassing the breakdown voltage of these structures, which is then equal to the observed barrier potential. Previous experiments exploring the microscopic structure of the laser written wires via scanning and transmission electron microscopy have shown multiple intersecting planes of graphitic sheets with a thickness of 40-100 nm [19,20]. It was found that only ≈4% of the wire cross-sectional area contained conductive sp 2 bonded carbon, while the remainder was unmodified diamond.…”
Section: Discussionmentioning
confidence: 97%
“…High resolution transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) performed by Patrick Salter's group on thin FIB milled cross section areas of the laser written tracks showed a non-uniform structural modification consisting of about 4% of sp 2 bonded carbon [87], as shown in figures 7(d) and (e). The tracks were written using a femtosecond Ti:Sapphire laser at 1 kHz repetition rate focused 4 μm beneath the surface.…”
Section: Optimization Of Femtosecond Laser-written Structures For Phomentioning
confidence: 99%
“…(c) Micro-Raman spectra (normalized to the G-peak) in the center of the modification tracks written with repetition rates of 5, 25 and 500 kHz, with pulse energy being constant (800 nJ)[85]. (d) Scanning transmission electron microscopy (STEM) image of FIB milled cross section of laser induced tracks[87]. (e) Spatial distribution of sp 2 bonding in the cross-sectional region defined as 'image' in (d).…”
mentioning
confidence: 99%